Quantum information theory - Wilde, Mark. (Cambridge: Cambridge University Press, 2017)
In this new edition, readers can expect to find over 100 pages of new material, including detailed discussions of Bell's theorem, the CHSH game, Tsirelson's theorem, the axiomatic approach to quantum channels, the definition of the diamond norm and its interpretation, and a proof of the Choi-Kraus theorem. Discussion of the importance of the quantum dynamic capacity formula has been completely revised, and many new exercises and references have been added.
Includes bibliographical references (pages 733-753) and index.
Keywords: Quantum computers; Quantum communication; Information theory -- Data processing; Electronic data processing -- Technological innovations